Internalisasi Kecerdasan Emosional Peserta Didik dalam Proses Pembelajaran di SMA Negeri 1 Metro - Hanwar Priyo Handoko (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2019)
Emotional intelligence is a new paradigm in education that will give hope of optimal success in the learning process; emotions play an important role in life. This is what increasingly stirred researchers to conduct this research. With the formulation of the problem as follows: How is the internalization of emotional intelligence in the learning process in school. The purpose is to examine how the values ​​of emotional intelligence in students are planted. This type of research is a qualitative descriptive study using the techniques of collecting data on interviews, observation and documentation. While the data analysis technique uses a method of classifying data and inductive conclusions. From the results of the research that has been done it can be concluded that the moral akidah teachers have instilled emotional intelligence in their students both when teaching and learning activities are taking place or when they are outside of school hours. But seeing the level of emotional intelligence of the students was declared low.